Dynamical analysis of dispersal impact on a three-patch based predator-prey system with strong Allee effected preys - S. Biswas; D. Pal; P.K. Santra; G. S. Mahapatra (Mathematics in Applied Sciences and Engineering)
This paper describes a three-patch based predator-prey interaction model where a strong Allee effect accomplishes each prey species in their respective patches. It is also assumed that only the prey species are movable among the patches following the balanced dispersal rule. The stability behavior at the inner equilibrium point has been studied in the presence and non-existence of dispersal. This study also observes a vital characteristic of the Allee edge regarding the stability of the equilibrium of the model when prey species progress freely in their patches. Also, the dispersal can destabilize the interior equilibrium of populations, i.e., if the interior equilibrium becomes unstable in the absence of dispersal under some conditions, it becomes stabilized under some conditions whenever the prey species move among their patches. The Hopf bifurcation behavior of the system has been studied and numerical simulations have been performed taking hypothetical parameter values using MATHEMATICA and MATLAB software.